UPAYA MENINGKATKAN KOMPETENSI KEPALA SEKOLAHDALAM MANAJEMEN BANTUAN OPERASIONAL SEKOLAH (BOS) YANG TRANSPARANSI DAN AKUNTABEL MELALUI MODEL GROW MEDI SEKOLAH BINAAN - Erdita Erdita (Universitas Negeri Medan, 2019)
Abstract:Efforts to Improve Principal Competence in School Operational Assistance Management (Bos), which is Transparency and Accountability through the Model of Growing Mediated Schools. Determination of the place of research is based on the main focus of this research is the compilation of School Budget Activities and Budgets (RKAS) and BOS reporting carried out by the Principal as Chair of the BOS Management Team in accordance with the technical guidelines for the use of BOS and to assist School Principals in managerial competencies especially in the BOS financial sector. . Seen from the results of observations, guidance and examination of documents it appears that the average value of the observed aspects gets